2016
DOI: 10.1371/journal.pone.0150978
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhosis and Advanced Fibrosis in Hispanics in Texas: The Dominant Contribution of Central Obesity

Abstract: Liver cirrhosis is a leading cause of death in Hispanics and Hispanics who live in South Texas have the highest incidence of liver cancer in the United States. We aimed at determining the prevalence and associated risk factors of cirrhosis in this population. Clinical and demographic variables were extracted for 2466 participants in the community-based Cameron County Hispanic Cohort in South Texas. Aspartate transaminase to Platelet Ratio Index (APRI) was used to predict cirrhosis in Cameron County Hispanic Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…Plasma samples were also collected from 96 participants of the Cameron County Hispanic Cohort (CCHC) with aspartate transaminase (AST) to platelet ratio index (APRI) scores !1, indicative of the presence of cirrhosis/advanced fibrosis. The demographic and clinical parameters of the 96 CCHC subjects were described previously (7). All these subjects were enrolled in 4 Texas counties with high rates of liver cancer.…”
Section: Patients and Biospecimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma samples were also collected from 96 participants of the Cameron County Hispanic Cohort (CCHC) with aspartate transaminase (AST) to platelet ratio index (APRI) scores !1, indicative of the presence of cirrhosis/advanced fibrosis. The demographic and clinical parameters of the 96 CCHC subjects were described previously (7). All these subjects were enrolled in 4 Texas counties with high rates of liver cancer.…”
Section: Patients and Biospecimensmentioning
confidence: 99%
“…Other risk factors contributing to HCC include chronic hepatitis B or C virus (HBV, HCV) infection, alcohol abuse, nonalcoholic steatohepatitis (NASH) and aflatoxin exposure (6). We previously reported that the prevalence of cirrhosis in Hispanics in South Texas is 0.94%, which is 4-fold higher than the national prevalence (7). Risk factors independently associated with cirrhosis in this population are central obesity, diabetes, HCV, and alcohol with a remarkable population attributable fraction of 65.3% from central obesity.…”
Section: Introductionmentioning
confidence: 99%
“…CCHC is a population‐based Mexican‐American cohort in South Texas, with high rates of obesity, NAFLD, and HCC. ( 16‐19 )…”
mentioning
confidence: 99%
“…23 A long-standing, largely Mexican-American prospective cohort of patients in South Texas highlights the profound net impact of obesity and excess alcohol consumption, as well as potential genetic and environmental factors: in those men with central adiposity and alcohol use, advanced fibrosis or cirrhosis developed in 12.5% of all patients, at a median 30 years of age. 24 Interestingly, our data demonstrate better patient and graft survival for Hispanic LT recipients as compared with white patients on multivariable analysis. A similar observation has also been reported in a recent analysis for both LT alone and liver-kidney recipients.…”
Section: Characteristics Of Lt Recipients With Bashmentioning
confidence: 58%